The Impact of COVID-19 Pandemic on the Financial Performance of Firms on the Indonesia Stock Exchange - Sunitha Devi; Ni Made Sindy Warasniasih; Putu Riesty Masdiantini; Lucy Sri Musmini (Universitas Hayam Wuruk Perbanas, 2020)
The COVID-19 pandemic has harmed the national economy and caused a decline in various businesses' financial performance. This study aims to examine the impact of the COVID-19 pandemic on firms' financial performance listed on the Indonesia Stock Exchange. The research samples included 214 companies, which were divided proportionally into nine sectors or 49 sub-sectors. Data analysis used was the Wilcoxon Signed Rank Test. The results show an increase in the leverage ratio and short-term activity ratio but a decrease in the public companies' liquidity ratio and profitability ratio during the COVID-19 pandemic. There was no significant difference in the liquidity ratio and leverage ratio. However, the public companies' profitability ratio and short-term activity ratio differed significantly between before and during the COVID-19 pandemic. The sector that experienced an increase in liquidity ratio, profitability ratio, and short-term activity ratio but a decrease in the leverage ratio was the consumer goods sector. In contrast, the sectors experiencing a decrease in the liquidity and profitability ratios were property, real estate and building construction, finance, trade, services, and investment sectors.